PENGARUH INFUSA DAUN KELOR (Moringa oleifera) SEBAGAI PRESERVATIF ALAMI TERHADAP KUALITAS DAGING BABI - Selviani Trivoningsi Dangur; Novalino H. G. Kallau; Diana Agustiani Wuri (JURNAL KAJIAN VETERINER, 2020)
Pork is one of the most consumption types of meat in the East Nusa Tenggara region.. Moringa leaf are one part of the plant which is known to have antimicrobial compounds.The aimof this research was to determine the influence of Moringa leaf infusion as a natural preservative to the quality of pork.This research is an experimental laboratory research and used a total of 48 samples of thigh pork (Biceps femoris). This research used a completely randomized design with factorial pattern. The first factor was concentration of infusion Moringa leaf consist of 0% (K0), 5% (K1), 10% (K2), and 15% (K3) and the second factor was time of storage consist of 0,6, 12, and 18 hours with 3 replications. The parameters of porkquality that have been examined: color, texture, odor, value in the Eber test, pH value, and total plate count (TPC) value.The results showed that the addition of Moringa leaf infusion change the color and odor. The Eber test shows the K3 group can last up to 18 hours. There was no significant effect of infusion concentration (P> 0.05) on the pH value and there was a very significant effect on the time of storage (P<0.01) on the pH value. There was a significant effect of infusion concentration (P<0.05) and very significant effect on the time of storage (P <0.01) on the TPC value. The value of TPC in the K3 group was below of the Standar Nasional Indonesia contamination limit for laying less than 12 hours at room temperature.